Mengoptimalkan Digital Marketing Dalam Transformasi Digital : Membangun Bisnis Masa Depan - Hartini, Hartini; Wahyuningsih, Hartati Dyah; Paryanta, Paryanta; Zamri, Rivqi Maulana (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
In an increasingly advanced digital era, digital transformation has become a crucial necessity for businesses aiming to remain competitive and relevant. One of the key components of digital transformation is digital marketing, which plays a vital role in expanding market reach, enhancing customer interaction, and optimizing overall business strategies. This research discusses how digital marketing can be optimized to support digital transformation, involving the utilization of technologies such as big data and artificial intelligence (AI), personalized content, and the implementation of multichannel marketing strategies. By integrating digital marketing into digital transformation, businesses can create more personalized and effective customer experiences, maintain loyalty, and ensure sustainability and growth in the future. Through a data-driven approach and continuous innovation, digital marketing can be a powerful tool for winning competition in an increasingly dynamic business world.